Electric vehicles adoption challenges in Oman: a comprehensive assessment and future prospects for sustainable cities - Ahmed, Umar; Fida, Bashir Ahmad; Thumiki, Venkat Ram Raj; Hamdun Al Marhoobi, Sauda Salim (Frontiers in Sustainable Cities, 2024)
The rising popularity of Electric Vehicles (EVs), fuelled by technological advancements and supportive government policies, presents a promising solution to reduce carbon emissions from conventional cars. This study explores public perceptions of obstacles to Electric Vehicle (EV) adoption in Oman and assesses EVs' impact on city sustainability. Over 300 car consumers in Muscat participated in a survey, facilitated through Microsoft Forms, and distributed via email and social media platforms like WhatsApp, Facebook, LinkedIn, and Instagram. Data analysis utilized descriptive statistics and Structural Equation Modelling (SEM). The study finds that the main obstacles to EV adoption in Oman include a lack of public charging infrastructure, limited EV knowledge, and concerns about available EV models. Safety issues, financial constraints, and low public awareness of climate change also hinder adoption. Structural SEM results show positive correlations between cost-effectiveness, charging infrastructure availability, climate change awareness, and intention to adopt EVs. However, safety concerns negatively impact EVs purchase intention. Regarding the impact of EVs on Oman's cities, respondents generally believe in the potential for EVs to improve air quality, enhance urban living conditions, and mitigate noise and air pollution. However, the respondents were also cautious about the widespread use of EVs due to the high infrastructure investment costs and energy consumption. Therefore, this study recommends targeted interventions like awareness campaigns, better charging infrastructure, and adoption incentives. These insights are vital for policymakers and stakeholders aiming to promote sustainable EV adoption in Oman and beyond.